2010
DOI: 10.1016/j.cub.2009.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Moribund Ants Leave Their Nests to Die in Social Isolation

Abstract: Animal societies provide perfect conditions for the spread of infections and are therefore expected to employ mechanisms that reduce the probability of transmitting pathogens to group members [1-4]. Death in nature rarely results from old age but commonly results from diseases. Leaving one's group to die in seclusion might be an efficient way of minimizing the risk of infecting kin. Anecdotal observations of moribund individuals deserting from their groups exist for several species, including humans (e.g., [5]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
195
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(204 citation statements)
references
References 22 publications
8
195
1
Order By: Relevance
“…While theoretical work convincingly revealed the conditions required for host suicide to evolve [39,40], empirical work has often been criticized [41,42]. In particular, the adaptive significance of host suicide has been challenged because studies involved eusocial Hymenoptera [43][44][45] or clonal aphids [46], where complex life histories impeded rigorous fitness tests and the exclusion of agarose concentration in growth medium bacterial cultures went extinct ** *** *** *** *** * *** *** *** *** ** *** *** *** *** Figure 3. (a) On solid agarose (0.4%, high relatedness) Escherichia coli l significantly outcompeted E. coli HK97 at all phage concentrations, even when initially rare (t-tests, from left to right: t 7 ¼ 3. rspb.royalsocietypublishing.org Proc R Soc B 280: 20123035 alternative explanations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While theoretical work convincingly revealed the conditions required for host suicide to evolve [39,40], empirical work has often been criticized [41,42]. In particular, the adaptive significance of host suicide has been challenged because studies involved eusocial Hymenoptera [43][44][45] or clonal aphids [46], where complex life histories impeded rigorous fitness tests and the exclusion of agarose concentration in growth medium bacterial cultures went extinct ** *** *** *** *** * *** *** *** *** ** *** *** *** *** Figure 3. (a) On solid agarose (0.4%, high relatedness) Escherichia coli l significantly outcompeted E. coli HK97 at all phage concentrations, even when initially rare (t-tests, from left to right: t 7 ¼ 3. rspb.royalsocietypublishing.org Proc R Soc B 280: 20123035 alternative explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Possible examples include the observation that infected social insect workers leave the colony to die in isolation (i.e. altruistic self-removal [44,45]), a behaviour that could come at negligible costs because infected individuals might be strongly compromised in carrying out worker tasks anyway.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive suicide in social insects is relatively common as a pre-emptive strategy (e.g. honeybees using their stings to defend the colony), although it is notably difficult to evaluate in the context of host-parasitoid interactions [29,[35][36][37][38][39]. The host suicide hypothesis postulates that mature parasitoids emerging from hosts are more likely to infect host's kin than non-kin.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that dying ants will leave their nests or are restricted entry to their nests [29]. To determine whether M. xipe beetles are able to selectively locate individual parasitized ants within the coffee plantation, we constructed beetle traps from small plastic cups with plaster of Paris on the bottom to retain moisture and lids with holes large enough for the beetles to enter the traps (electronic supplementary material, S3).…”
Section: (C) Beetle Trap Experimentsmentioning
confidence: 99%
“…auto-and allogrooming, alloor self-exclusion of infected individuals, corpse disposal and/or cemetery formation (Oi and Pereira, 1993;SchmidHempel, 1998;Heinze and Walter, 2010). However, increasing frequency of allogrooming, while reducing the amount of spores on individual level, may assist the spread of pathogens among nest-mates (Oi and Pereira, 1993;Reber et al, 2011;Konrad et al, 2012).…”
Section: Exploitation Of Ant Individuals: Ectoparasites Endoparasitementioning
confidence: 99%